(untitled) (Western European Journal of Historical Events and Social Science, 2026)
This article examines the contribution of the scholars of Mawarannahr to world civilization through the interconnected processes of knowledge production, intellectual systematization, and transregional transmission. Historically known as Transoxiana, Mawarannahr emerged as one of the major centers of Muslim civilization in the medieval period and became closely associated with such cities as Bukhara and Samarkand. The purpose of the study is to analyze how the scholars of this region influenced world civilization through original scholarship, the organization of inherited knowledge into durable systems, and the circulation of their works across cultural and linguistic boundaries. The study applies historicalcomparative, textual-analytical, and intellectual-historical methods. The results show that the scholars of Mawarannahr made a multidimensional contribution to world civilization. First, they generated original scientific and theological knowledge. Second, they transformed diverse bodies of knowledge into systematic and teachable intellectual frameworks. Third, their works entered wider Islamic and, in some cases, European traditions through translation, commentary, institutional teaching, and long-term scholarly reception. The cases of al-Farghani, Ibn Sina, al-Bukhari, al-Maturidi, and Ulugh Beg confirm that Mawarannahr should be regarded not as a peripheral region, but as a major intellectual center of the premodern world. The article also emphasizes that the region’s importance lay not only in individual genius, but in the scholarly environment that enabled knowledge to be produced, preserved, and transmitted across civilizations.